JURIDICAL IMPLICATIONS OF THE SUPREME COURT'S DECISION NUMBER: 121 K/TUN/2017 ON DISCLOSURE OF DATA INFORMATION OF THE HOLDER RIGHT TO CULTIVATE - I Gede Cahya Widiangga; I Wayan Wesna Astara; I Nyoman Alit Puspadma (NOTARIIL Jurnal Kenotariatan, 2022)
The legal construction of Articles 187 and 191 of the Minister of Agrarian Affairs Number 3 of 1997 and Article 12 paragraph (4) letter i of the Perka BPN excludes HGU documents as documents that are not accessible to the public and can only be given to government agencies.This study aims to examine regulation of information transparency on the data of the holder of the Right to Cultivate and to examine the legal consequences of not implementing the Supreme Court's Decision Number: 121 K/TUN/2017 by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) which has permanent legal force. This study uses a normative juridical method according to the applicable law. The results of this study revealed that Transparency of information on data on holders of the Right to Cultivate refers to Article 2 paragraph (1) of Government Regulation Number 24 of 1997 concerning Land Registration (hereinafter referred to as PP No. 24 of 1997) which stipulates that public information is open and accessible to every user of public information. The Right to Cultivate Documents are not exempt under Article 17 letters b and h of the KIP Law. Furthermore, the legal consequences of not implementing the Supreme Court's decision Number: 121 K/TUN/2017, namely the cassation respondent may be subject to administrative sanctions in accordance with Article 116 of the Administrative Court Law and criminal sanctions in accordance with Article 52 of the KIP Law.